Perceptions and morbidity profile among women beedi workers: a cross-sectional study - Swetha, Dava; Naga Gayathri, Batchu; Gunda, Sandhya (International Journal Of Community Medicine And Public Health, 2025)
Background: Beedi rolling is a major source of income for rural women in India but exposes them to tobacco dust and ergonomic strain, leading to considerable morbidity. Misconceptions regarding its safety and poor awareness of welfare schemes aggravate the problem. Objectives were to assess the perceptions regarding occupational hazards and to document the morbidity profile among women beedi workers. Methods: A descriptive cross-sectional study was conducted among 181 selected women beedi workers in Nizamabad from January to March 2025. Data on socio-demographics, perceptions, and self-reported morbidities were collected using a pre-tested questionnaire. Descriptive statistics like frequency and percentages were calculated. Results: Among participants, 29.3% were under the age group 15-24 years and 61.3% were married. While 62.4% recognized that tobacco dust is harmful, only 15.5% reported using protective gear. A significant proportion (50.3%) perceived beedi rolling as safe due to its home-based nature. Common morbidities included musculoskeletal pain (60.8%), headache (49.7%), chronic cough (45.9%), breathlessness (34.3%), eye irritation (30.9%), skin problems (19.3%), and menstrual irregularities (13.8%). Awareness of government welfare schemes was low (19.9%), yet 60.2% expressed willingness to leave beedi rolling if alternative livelihoods were available. Conclusions: Women beedi workers exhibit a high burden of musculoskeletal and respiratory morbidity alongside partial awareness of occupational hazards and limited adoption of protective practices. There is an urgent need for targeted health education, ergonomic interventions, improved dissemination of welfare schemes, and the development of sustainable alternative livelihoods.